THE DEVELOPMENT OF ISLAMIC LAW: A CASE STUDY OF MALIKI’S RULES ON MUDARABAH - Shaharuddin, Amir (Jurnal Syariah, 2010)
This article examines the development of Maliki’s rules on mudarabah between the period of second and seventh century Hijri. The examination was executed by analysing five Maliki’s legal texts namely al-Muwatta’ of Malik (d.179), al-Mudawwanah al-Kubra of Sahnun (d.240), al-Kafi fi Fiqh Ahl al-Madinah of Ibn ‘Abd al-Barr (d.463), Bidayah al-Mujtahid of Ibn Rushd (d.595) and al-Dhakhirah of al-Qarafi (d.684). It was discovered that the text of al-Mudawwanah al-Kubra represented the most comprehensive discussion of Maliki’s rules on the said subject. The Maliki’s jurists after Sahnun did not produce significant new rules on mudarabah but organized the topic systematically. Hence, the discussion concluded that Islamic commercial law within the Maliki’s school reaches its maturity since the third century Hijri. The finding implies that the school has a complete legal text nearly two centuries earlier than the Shafi‘i’s.